Description of a new species, Xiphodolamia maliki sp. nov. and the shark teeth of Middle Eocene (Lutetian) aged Soğucak Formation in Küçükçekmece, Istanbul, Turkey - Artüz, M. Levent; Sakinç, Mehmet (Zootaxa, 2025)
In 1954–1955, the prominent geologist, Ord. Prof. Malik Sayar (1862–1965) from the Geological Sciences Institute at Istanbul Technical University (ITU), collected fossil shark teeth from the Eocene deposits of Küçükçekmece, Turkey, specifically the Soğucak Formation. The İhsan Ketin Museum at ITU preserved these teeth for decades. Among the collection, 31 teeth belong to Macrorhizodus cf. praecursor, 2 to Otodus sokolovi, 44 to the genus Xiphodolamia, and 43 remain unidentified, for a total of 120 teeth. Xiphodolamia spp. are rare in the fossil record and are represented solely by isolated teeth. This study aims to reclassify the museum specimens that were previously identified at the genus level as Lamna sp. to compare the teeth of the Xiphodolamia genus with other classified members of this genus and to highlight the differences that warrant renaming these specimens as Xiphodolamia maliki sp. nov. For this purpose, the morphology and internal tooth structure of these teeth, collected by Malik Sayar from the Küçükçekmece Eocene deposits, were compared with those of teeth sourced from different origins. In addition, this paper documents other teeth collected by Malik Sayar from the Lutetian-aged Soğucak Formation of the Eocene Epoch and provides information on the geological context, the palaeoecology of the formation, and the autecology of the species.